2007
DOI: 10.1007/bf03191006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro binding of lidocaine to liver tissue under the influence of propranolol: Another mechanism of interaction?

Abstract: The co-administration of lidocaine and propranolol leads to significant drug-drug interactions. Beta-blockers decrease liver perfusion and inhibit the activity of hepatic microsomal lidocaine metabolizing enzymes of the P450_2D subfamily. Hence, there is a resulting reduction in the hepatic breakdown of lidocaine and an increase in its serum concentrations. In this study the ability of propranolol to displace lidocaine from its binding sites in liver tissue has been examined through an in vitro model. Rat live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…Both drugs are known to possess a higher affinity of binding to alpha-acid glycoprotein than to albumin, but in clinical practice only the amount of the free active fraction is important, since this is responsible for the pharmacological effect. These results are in agreement with previous studies in which co-administration of other cationic drugs was shown to increase the concentration of free lidocaine in serum and tissues (2,9).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Both drugs are known to possess a higher affinity of binding to alpha-acid glycoprotein than to albumin, but in clinical practice only the amount of the free active fraction is important, since this is responsible for the pharmacological effect. These results are in agreement with previous studies in which co-administration of other cationic drugs was shown to increase the concentration of free lidocaine in serum and tissues (2,9).…”
Section: Discussionsupporting
confidence: 93%
“…It has been previously demonstrated that lidocaine and propranolol are eliminated via hepatic metabolism (2). Lidocaine, after its absorption, is transported from plasma proteins forming a drug-protein complex, which represents a latent store of the drug.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…β-Blockers decrease liver perfusion and inhibit the activity of hepatic microsomal lidocaine metabolizing enzymes of the P450 2D subfamily, resulting in a reduction in the hepatic breakdown of lidocaine and an increase in its serum concentrations. Propranolol significantly decreases the binding process of lidocaine in liver tissue by displacing it from liver proteins, and therefore the coadministration of the two drugs may increase the free fraction of lidocaine excreted by the liver (Tesseromatis et al, 2007).…”
Section: Drug Displacement Interactions (Ddis)mentioning
confidence: 99%